Perbedaan Pola Asupan Kalori Makanan terkait Obesitas pada Geriatri - Saputra, Rifaldi; Sigar, Tiara Regina Beatriks; Lorensia, Amelia (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2023)
The rapid increase in the population growth of the elderly (geriatrics) is one of the characteristics of the 21stcentury population. In 2000 the total geriatric population worldwide reached 426 million or around 6.8% of thetotal population. The increase in the geriatric population in Indonesia was predicted long ago. The increase inthe geriatric population has created a public health problem, namely the high morbidity rate. Obesity was foundto be one of the factors manifesting in caloric intake. This study aims to determine differences in calorie intakeand differences in BMI in obese and non-obese geriatrics. In this study using a retrospective method bycollecting respondents using purposive sampling. Variables to be examined include: food calorie intake usingthe 24-Hour Recall method and Body Mass Index. The respondents of this study consisted of 76 respondents inthe obese geriatric group and 76 respondents in the non-obese geriatric group. The results of different tests onfood calorie intake in the obese and non-obese geriatric groups showed a value of p = 0.000. The conclusionobtained in this study is that there is a significant difference in caloric intake in the obese and non-obesegeriatric groups.